Search for the Standard Model Higgs boson decaying into bb[bar] produced in association with top quarks decaying hadronically in pp collisions at √s = 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Journal of high energy physics, 2016)
A search for Higgs boson production in association with a pair of top quarks (tt¯H$$ t\overline{t}H $$) is performed, where the Higgs boson decays to bb¯$$ b\overline{b} $$, and both top quarks decay hadronically. The data used correspond to an integrated luminosity of 20.3 fb−1 of pp collisions at s=8$$ \sqrt{s}=8 $$TeV collected with the ATLAS detector at the Large Hadron Collider. The search selects events with at least six energetic jets and uses a boosted decision tree algorithm to discriminate between signal and Standard Model background. The dominant multijet background is estimated using a dedicated data-driven technique. For a Higgs boson mass of 125 GeV, an upper limit of 6.4 (5.4) times the Standard Model cross section is observed (expected) at 95% confidence level. The best-fit value for the signal strength is μ = 1.6 ± 2.6 times the Standard Model expectation for mH = 125 GeV. Combining all tt¯H$$ t\overline{t}H $$searches carried out by ATLAS at s=8$$ \sqrt{s}=8 $$and 7 TeV, an observed (expected) upper limit of 3.1 (1.4) times the Standard Model expectation is obtained at 95% confidence level, with a signal strength μ = 1.7 ± 0.8.